2016
DOI: 10.3414/me15-01-0142
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Mining of Comorbid Neurodevelopmental Disorders Using the SPADE Algorithm

Abstract: SummaryObjectives: Understanding the progression of comorbid neurodevelopmental disorders (NDD) during different critical time periods may contribute to our comprehension of the underlying pathophysiology of NDDs. The objective of our study was to identify frequent temporal sequences of developmental diagnoses in noisy patient data. Methods: We used a data set of 2810 patients, documenting NDD diagnoses given to them by an NDD expert at a child developmental center during multiple visits at different ages. Ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…All measures found that in each iteration, all patterns were similar at a signi cance level of P < 0.05. All Pearson and Spearman correlation coe cients are higher than 0.75 [19] , and the smallest correlation coe cient is 0.89, which means that the metric values in the training and validation sets are similar. The p-values of the Kolmogorov-Smirnov tests for the similarity of the distributions are all above 0.7, so no signi cant difference is found in the distributions.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…All measures found that in each iteration, all patterns were similar at a signi cance level of P < 0.05. All Pearson and Spearman correlation coe cients are higher than 0.75 [19] , and the smallest correlation coe cient is 0.89, which means that the metric values in the training and validation sets are similar. The p-values of the Kolmogorov-Smirnov tests for the similarity of the distributions are all above 0.7, so no signi cant difference is found in the distributions.…”
Section: Discussionmentioning
confidence: 96%
“…[15][16][17] Recently, many studies have focussed on developing sequential pattern mining methods to discover real-world treatment behaviour patterns from clinical data, which has become a research hotspot. [18][19][20] Although current research mainly focuses on the mining of drug treatment models. [21][22][23] For example, Wright A P et al used sequential pattern mining to evaluate whether the method could effectively identify temporal relationships between diabetes drugs.…”
Section: Highlightsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most process mining algorithms can automatically build process patterns, which are very suitable for understanding and can be used for process optimization [15][16][17] . Recently, many studies have focused on developing sequential pattern mining methods to discover real-world treatment behavior patterns from clinical data, which has become a research hotspot [18][19][20] . However, current research focuses on the mining of drug treatment models [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%